In Vitro Cadmium-Induced Alterations in Growth and Oxidative Metabolism of Upland Cotton (Gossypium hirsutum L.). (11th June 2014) - Daud, M. K.; Mei, Lei; Najeeb, Ullah; Khan, Muhammad Azim; Deeba, Farah; Raza, Irum; Batool, Aliya; Zhu, S. J.
Abstract : Cadmium (Cd) is a toxic pollutant, which cause both dose- and time-dependent physiological and biochemical alterations in plants. The present in vitro study was undertaken to explore Cd-induced physiological and biochemical changes in cotton callus culture at 0, 550, 700, 850, and 1000  μ M Cd for four different stress periods (7, 14, 21, and 28 days). At 1000  μ M Cd, mean growth values were lower than their respective control. The cell protein contents decreased only after 7-day and 14-day stress treatment. At 550  μ M Cd, malondialdehyde (MDA) contents decreased after various stress periods except 21-day period. Superoxide dismutase (SOD) activity at 1000  μ M Cd improved relative to its respective controls in the first three stress regimes. Almost a decreasing trend in the hydrogen peroxide (H2 O2 ) and peroxidase (POD) activities at all Cd levels after different stress periods was noticed. Ascorbate peroxidase (APX) activity descended over its relevant controls in the first three stress regimes except at 700  μ M Cd after 14- and 21-day stress duration. Moreover, catalase (CAT) mean values significantly increased as a whole. From this experiment, it can be concluded that lipid peroxidation as well as reactive oxygen species (ROS) production was relatively higher as has been revealed by higher MDA contents and greater SOD, CAT activities.